(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
This study aimed to evaluate the morphological, physiological, and biochemical responses of local wheat ("Sateni-22") under salinity stress and to assess its phytodesalination potential. Experiments were conducted under controlled conditions using different NaCl concentrations. The results showed that under conditions of low NaCl concentrations, as a result of the activation of adaptive mechanisms, morphophysiological indicators were able to be somewhat preserved, but at high concentrations they were significantly reduced. It should also be noted that, in parallel with the increase in salinity, the content of Na⁺ and Cl⁻ ions in the above-ground organs of the plant significantly increased. These findings indicate a moderate adaptive capacity of local wheat and its potential efficiency for soil phytodesalination in saline environments.